The emerging threat of fluroquinolone-, bedaquiline-, and linezolid-resistant Mycobacterium tuberculosis in China: Observations on surveillance data - Shanshan Li; Yaoju Tan; Yufeng Deng; Guanghong Bai; Mingxiang Huang; Yuanyuan Shang; Yufeng Wang; Zhongtan Xue; Xuxia Zhang; Wei Wang; Junhua Pan; Yu Pang (Elsevier, 2024)
Background: Drug-resistant tuberculosis (TB), especially multidrug-resistant tuberculosis (MDR-TB), constitutes a major obstacle to fulfill end TB strategy globally. Although fluoroquinolones (FQs), linezolid (LZD) and bedaquiline (BDQ) were classified as Group A drugs for MDR-TB treatment, our knowledge of the prevalence of TB which were resistant to Group A drugs in China is quite limited. Methods: In this study, we conducted a prospective multicenter surveillance study in China to determine the proportion of TB patients that were resistant to Group A drugs. A total of 1877 TB patients were enrolled from 2022 at four TB specialized hospitals. The drug susceptibility of isolated strains was conducted using the MGIT 960 system and the molecular mechanisms conferring drug resistance were investigated by Sanger sequencing. Results: 12.9% of isolates were resistant to levofloxacin (LFX), 13.2% were resistant to moxifloxacin (MOX), 0.2% were resistant to bedaquiline (BDQ), and 0.8% were resistant to linezolid (LZD). Totally, 14.0% and 0.4% were classified as multidrug resistant- (MDR-) and extensively drug resistant- (XDR-) TB. The drug resistance was more common in retreated TB cases compared to new cases. In addition, 70.0% of fluoroquinolone (FQ)-resistant isolates harbored mutations in the gyrA and gyrB gene. By contrast, the common drug-resistant mutations were only found in 50% BDQ-resistant and 20% LZD-resistant isolates. Conclusions: Our data demonstrate that approximate half of MDR -TB patients are resistant to fluoroquinolones, with extremely low prevalence of initial BDQ and LZD resistance. Findings from this study provide important implications for the current management of MDR-TB patients.